IMPLEMENTASI METODE TOPSIS TERHADAP PEMILIHAN BUPATI CIAMIS (STUDI KASUS MAHASISWA ASAL CIAMIS) - Rahayu, Sri; Warnilah, Ai Ilah (LPPM Universitas Nusa Mandiri, 2019)
One form of democracy in Indonesia, on June 27, 2018 regional elections would be held simultaneously in various region in Indonesia. Among them was Ciamis Regency which organized the Election of Regents and their representatives. In the selection of leaders there were often election violations. Seeing this condition, the author wanted to analyze the voters’ assessment of the candidate paired whether in accordance with the results of the election or not by implementing the Technique for Order Preference by Similarity to Ideal Solution decision-making method in the election of regents and representatives in 2018 based on observations made to 100 students from Ciamis who had the right to vote in the Regional Head Election in 2018 from various Universities whose data was collected by questionnaire using purposive sampling. This research produces candidate number 1 pair of pair H. Herdiat Sunarya and Yana Diana Putra get value 0,691490149 higher than candidate number 2 H. Iing Syam Arifin and H. Oih Burhanudin who get value 0,308509851, the results of this study as well as the vote count recapitulation of the election of Regent and Vice Regent of Ciamis by KPU (General Election Commission) Ciamis Regency on July 5, 2018 starting at 9.00 pm – 23:00 pm ie the most votes achieved by the candidate number 1